THE EFFECT OF ENVIRONMENTAL MANAGEMENT ACCOUNTING ON ENVIRONMENTAL PERFORMANCE WITH GREEN PROCESS INNOVATION AS A MEDIATING - Clyde, Vierina; Puspanita, Intan; Vinta Desi, Anistya (JURNAL EKBIS, 2025)
This paper analyzes the Effect of Environmental management accounting on Environmental Performance with Green Process Innovation as a Mediating in manufacturing company of Banten Province. This research adopts quantitative method and survey method. This study relied on self-reported primary data from a self-administered survey by spreading questionnaires to 153 manufacturing companies in Banten Province. Three measurements were analyzed using structural equation modeling (SmartPLS 3.3). Three hypotheses were positively associated. The results of this study show that environmental management accounting have a positive effect on environmental performance, environmental management accounting have a positive effect on green process innovation, green process innovation can mediate the effect of environmental management accounting on environmental performance.